2022
DOI: 10.3390/su14127510
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Environmental Culture, Environmental Sustainability and Performance: The Mediating Role of Green HRM and Green Innovation

Abstract: This study investigated Environmental Sustainability (ES) and Environmental Performance (EP) through the direct and indirect use of Organizational Environmental Culture (OEC). This study focused on top managers, namely, the CEOs and directors of SMEs, along with their middle managers. In this study, the researchers employed green HRM and Green Innovation (GI) as mediators. We applied a quantitative approach that utilized cross-sectional data collected from Saudi Arabian Small and Medium-sized Enterprises (SMEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 91 publications
(172 reference statements)
1
7
0
Order By: Relevance
“…My findings corroborate with those found by Sobaih et al ( 2022 ) in Saudi context by using a green innovation and CSR as mediating variables to prove the effect of sustainability on corporate performance. The same affirmation on SMEs companies in Saudi Arabia is argued by Al Doghan et al ( 2022 ).…”
Section: Discussionsupporting
confidence: 66%
“…My findings corroborate with those found by Sobaih et al ( 2022 ) in Saudi context by using a green innovation and CSR as mediating variables to prove the effect of sustainability on corporate performance. The same affirmation on SMEs companies in Saudi Arabia is argued by Al Doghan et al ( 2022 ).…”
Section: Discussionsupporting
confidence: 66%
“…After validation of the measurement model, we conducted the "Variance Inflation Factor (VIF)" test on all variables making up the interaction conditions to mitigate the multicollinearity risk (Aiken et al, 1991), where all indicators are acceptable because they have values below 5 (Hair et al, 2018).…”
Section: Hypotheses Testingmentioning
confidence: 99%
“…Past studies have proven that GHRM has a favorable outcome on organizational performance (Obeidat et al , 2020), economic performance (Yong et al , 2022), enabling of green culture (Muisyo et al , 2022), EP (Obeidat et al , 2020; Yusoff et al , 2020) and social performance (Zaid et al , 2018). It was also found that GHRM is important in green OC and environmental sustainability due to its prominent role in reducing the adverse effects of energy consumption and hazardous emissions (Doghan et al , 2022). The growing literature on GHRM focused on quantifying the impacts of GHRM practices (green job analysis and description, green recruitment, green training, green performance management and green compensation) on various outcomes over the last decade.…”
Section: Literature Reviewmentioning
confidence: 99%